Turbulence in cavity acoustic black hole. (15th February 2022) - Liang, Xiao; Chu, Jiaming; Zhou, Zhuo; Hu, Congfang; Peng, Jinfeng; Liu, Baixi; Mo, Lin; Wu, Jiu Hui; Lin, Mei
Abstract: In this paper, we adopt both numerical and experimental approaches to investigate the turbulent flow in a cavity Acoustic Black Hole (ABH), and the low frequency sound energy dissipation mechanism under turbulence. Through the simulation by thermoviscous acoustic module, we deeply study the turbulent development process of the fluid acoustic medium in the cavity ABH, and how the turbulent evolution determines the acoustic performance of the ABH. This dissipation mechanism caused by turbulence in ABH enables cavity acoustic black hole to isolate more than 90% low frequency sound waves in an ultra-low and ultra-broad band, which can provide a good technical solution for the isolation of low frequency sound waves. Our experimental results not only prove our simulation and numerical results, but also prove an important theoretical result of turbulence theory, that is, in fully turbulence state, the relationship between turbulence energy spectral density E and wave number k ( k = 1/ L, L is the characteristic size L ) is E k −3 .